Focus and impact on poverty reduction, livelihoods, and jobs - CGIAR Initiative on NEXUS Gains (International Water Management Institute, 2024)
A NEXUS Gains impact area brief shares examples of how policy research and engagement in water, energy, food, and ecosystems can help to address rural poverty by increasing agricultural incomes and creating jobs.